Gifted students' perceptions about leadership and leadership development. (3rd July 2021) - Lee, Seon-Young; Matthews, Michael; Boo, Eunjoo; Kim, Yun-Kyoung
ABSTRACT: Although leadership is widely considered an aspect of giftedness, few studies have examined gifted students' beliefs regarding their own leadership abilities and their potential to become leaders. We developed a survey and administered it to a cross-cultural sample of 440 gifted and 303 non-identified secondary age participants to elicit their perceptions regarding good leaders and leadership, aspirations to become leaders, and expectations regarding leadership development for gifted students. Students overall expressed a preference for leaders who are able to provide a vision for the future and who care about others' feelings. Responses indicate that students believed honesty, social responsibility, and morality to be the most important characteristics of future leaders. Compared to non-identified students, we found that gifted students showed greater aspirations to become leaders, and their ultimate life goals and beliefs regarding leadership as a part of their talents was associated significantly with their leadership aspirations. We suggested how salient dimensions of cultural difference may have influenced some specific results observed for gifted students from South Korea versus the U.S. cultural context.